The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1128/jvi.76.22.11301-11311.2002
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Bursal Disease Virus Capsid Protein VP3 Interacts both with VP1, the RNA-Dependent RNA Polymerase, and with Viral Double-Stranded RNA

Abstract: Infectious bursal disease virus (IBDV) is a double-stranded RNA (dsRNA) virus of the Birnaviridae family. Its two genome segments are encapsidated together with multiple copies of the viral RNA-dependent RNA polymerase, VP1, in a single-shell capsid that is composed of VP2 and VP3. In this study we identified the domains responsible for the interaction between VP3 and VP1. Using the yeast two-hybrid system we found that VP1 binds to VP3 through an internal domain, while VP3 interacts with VP1 solely by its car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 43 publications
4
73
0
2
Order By: Relevance
“…The external surface of the particle is formed of trimeric subunits of VP2 (23,39), and the innermost layer is formed by trimeric subunits of VP3, the viral dsRNA, VP1, and VP4 (4,18). VP3, as predicted earlier, interacts with both segments of genomic dsRNA through its carboxy-terminal region (33,64,65), which also binds VP1 (40,63,64). The association of VP3 with viral dsRNA was also observed after extensive low-salt treatment of IPNV virions (29).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The external surface of the particle is formed of trimeric subunits of VP2 (23,39), and the innermost layer is formed by trimeric subunits of VP3, the viral dsRNA, VP1, and VP4 (4,18). VP3, as predicted earlier, interacts with both segments of genomic dsRNA through its carboxy-terminal region (33,64,65), which also binds VP1 (40,63,64). The association of VP3 with viral dsRNA was also observed after extensive low-salt treatment of IPNV virions (29).…”
Section: Discussionmentioning
confidence: 87%
“…In this scenario, as soon as it is synthesized, the newly replicated VPg-dsRNA may act as an initiation complex to trigger genome assembly by continuously nucleating capsid proteins. VP3 may play a key role in stabilizing the genomic dsRNA, where charged residues at its C terminus seem to be essential for this interaction, and to prompt proper particle assembly (9,47,64). In a proposed model for IBDV VLPs, VP3 needs to be activated by either genomic RNA or VP1 to FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Backbone atoms Heavy atoms (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) 0.41 Ϯ 0.18 1.49 Ϯ 0.44 (17)(18)(19)(20)(21)(22) 0.36 Ϯ 0.17 0.92 Ϯ 0.30 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) 0.77 Ϯ 0.33 1.63 Ϯ 0.48 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 0.87 Ϯ 0.39 1.14 Ϯ 0.40 (27)(28)(29)(30)…”
Section: Pairwise Rms Deviation (å)unclassified
“…VP3, the second major viral protein, binds the RNAdependent RNA polymerase VP1 and the genomic dsRNA (19,20). Birnaviruses present characteristic peptides associated to the virus particle (21).…”
mentioning
confidence: 99%
“…Previous information suggested that the inner capsid protein VP3 might be a suitable candidate in our search for an effective dominant-negative polypeptide. VP3 (28.8 kDa) controls the assembly of the major capsid polypeptide VP2 (7,8,10) and interacts with both the viral genome (4,14) and the virus-encoded RNA polymerase VP1 (5). Additionally, several VP3 functional domains have been mapped and characterized (4,5,7,14).…”
mentioning
confidence: 99%